Politics Backstage - Television Documentaries, Politics and Politicians - Bondebjerg, Ib (MedieKultur: Journal of media and communication research, 2006)
This article deals with "the transformation of visibility" in political discourse on and representation of politics and politicians in resent Dansih television documentaries. Drawing on the theories of Habermas, Meyrowitz and John B. Thompson, it is argued that the political persona on television is moved closer to the individual citizen, creating a sort "mediated quasi-inter- action" giving mediated communication a stronger element of face-to-face interaction. Together with the more pervasive "live" coverage of politics and politicians, this expands media coverage to both the backstage of political processes and the private and personal backstage of politicians, changing the form of democracy and public debate.